Modeling of the building local protection (shelter – in place) including sorbtion of the hazardous contaminant on indoor surfaces - Belyayev, N. N.; Rostochilo, N. V.; Nedopekin, F. V. (Science and Transport Progress, 2014)
Purpose. Chemically hazardous objects, where toxic substances are used, manufactured and stored, and also main lines, on which the hazardous materials transportation is conducted, pose potential sources of atmosphere accidental pollution.Development of the CFD model for evaluating the efficiency of the building local protection from hazardous substantives ingress by using air curtain and sorption/desorption of hazardous substance on indoor surfaces. Methodology. To solve the problem of hydrodynamic interaction of the air curtain with wind flow and considering the building influence on this process the model of ideal fluid is used. In order to calculate the transfer process of the hazardous substance in the atmosphere an equation of convection-diffusion transport of impurities is applied. To calculate the process of indoors air pollution under leaking of foul air Karisson & Huber model is used. This model takes into account the sorption of the hazardous substance at various indoors surfaces. For the numerical integration of the model equations differential methods are used. Findings. In this paper we construct an efficient CFD model of evaluating the effectiveness of the buildings protection against ingress of hazardous substances through the use of an air curtain. On the basis of the built model a computational experiment to assess the effectiveness of this protection method under varying the location of the air curtain relative to the building was carried out. Originality. A new model was developed to compute the effectiveness of the air curtain supply to reduce the toxic chemical concentration inside the building. Practical value. The developed model can be used for design of the building local protection against ingress of hazardous substances.